Analysis of cardiac autonomic modulation of children with attention deficit hyperactivity disorder - Carvalho, Tatiana Dias de; Wajnsztejn, Rubens; Abreu, Luiz Carlos de; Marques Vanderlei, Luiz Carlos [UNESP]; Godoy, Moacir Fernandes; Adami, Fernando; Valenti, Vitor Engrácia [UNESP]; Monteiro, Carlos B. M.; Laudio Leone, C.; Cruz Martins, Karen Cristina da; Ferreira, Celso (Dove Medical Press Ltd, 2014)
Background: Attention deficit hyperactivity disorder (ADHD) is characterized by decreased attention span, impulsiveness, and hyperactivity. Autonomic nervous system imbalance was previously described in this population. We aim to compare the autonomic function of children with ADHD and controls by analyzing heart rate variability (HRV).Methods: Children rested in supine position with spontaneous breathing for 20 minutes. Heart rate was recorded beat by beat. HRV analysis was performed in the time and frequency domains and Poincare plot.Results: Twenty-eight children with ADHD (22 boys, aged 9.964 years) and 28 controls (15 boys, age 9.857 years) participated in this study. It was determined that the mean and standard deviation of indexes which indicate parasympathetic activity is higher in children with ADHD than in children without the disorder: high frequency in normalized units, 46.182 (14.159) versus 40.632 (12.247); root mean square of successive differences, 41.821 (17.834) versus 38.150 (18.357); differences between adjacent normal-to-normal intervals greater than 50 milliseconds, 199.75 (144.00) versus 127.46 (102.21) (P<0.05); percentage of differences between adjacent normal-to-normal intervals greater than 50 milliseconds, 23.957 (17.316) versus 16.211 (13.215); standard deviation of instantaneous beat-to-beat interval, 29.586 (12.622) versus 26.989 (12.983).Conclusion: Comparison of the autonomic function by analyzing HRV suggests an increase in the activity of the parasympathetic autonomic nervous systems in children with ADHD in relation to the control group.
Keywords: attention deficit hyperactivity disorder; autonomic nervous system; children; heart rate variability